Choice of heat and moisture exchange filters for the 'in‐between size' paediatric patient. Issue 2 (15th November 2016) - Tan, Selene; Hee, Hwan Ing
Summary: We present a case of increased airway resistance due to the use of a small heat and moisture exchange filter (HMEF) in a 9‐year‐old male undergoing adenotonsillectomy. Paediatric HMEF size selection should be based on the tidal volume range as recommended by the manufacturer. In practice, however, it is more frequently based on the weight of the child. HMEF sizing based solely on the weight of the child may be inappropriate, especially for children who are 'in‐between sizes'. We highlight the important factors for consideration when selecting a paediatric HMEF.